Survey on image non-additive steganography - Yaofei WANG; Weiming ZHANG; Kejiang CHEN; Wenbo ZHOU; Nenghai YU (网络与信息安全学报)
Image non-additive steganography not only can better maintain the distribution of image elements, but also has high detection resistance.Firstly, the image non-additive image steganography methods were sorted out and divided into two major categories: non-additive distortion design and non-additive steganography coding design.The non-additive distortion was designed into three categories: theoretical models based, modification principles based and adversarial detection based, and compared these methods.Finally, the difficult problems faced by non-additive steganography and the future development ideas were analyzed.